2022
DOI: 10.1155/2022/6866925
|View full text |Cite|
|
Sign up to set email alerts
|

Blasting Law of Liquid CO2 Phase Change in Coal Mine Based on Numerical Simulation

Abstract: In order to obtain the best CO2 blasting drilling efficiency and improve the gas permeability coefficient of the coal seam in the mining area, a research method of liquid CO2 phase change blasting in the coal seam based on electrochemical numerical simulation is proposed. In this paper, the electrochemical numerical simulation of coalbed methane caused by liquid CO2 phase change blasting is studied through theoretical analysis, the antireflection mechanism of liquid carbon dioxide gas explosion on broken coal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Its characteristics fully meet the development needs of various countries on the coal industry. Because of the complexity of coal seam structure, many factors have led to the blasting cracking radius, which directly affect gas extraction [18,19]. Therefore, this topic has always been a focus of industry researchers to identify the factors affecting the liquid CO 2 phase change blasting cracking and to master methods to improve prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Its characteristics fully meet the development needs of various countries on the coal industry. Because of the complexity of coal seam structure, many factors have led to the blasting cracking radius, which directly affect gas extraction [18,19]. Therefore, this topic has always been a focus of industry researchers to identify the factors affecting the liquid CO 2 phase change blasting cracking and to master methods to improve prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…According to the abovementioned analysis, many studies focused on cumulative blasting, but the effect was not found to be sufficiently rational and required improvement. Many factors will affect the cracking effect of cumulative blasting, mainly due to the complex underground geographical environment, and the propagation law of cracks after blasting was found to be relatively complex and less controllable . At the same time, there are few data processing contents related to the numerical simulation of cumulative blasting, and it is impossible to express the characteristic law of multi-factor affecting the effect of cumulative blasting.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors will affect the cracking effect of cumulative blasting, mainly due to the complex underground geographical environment, and the propagation law of cracks after blasting was found to be relatively complex and less controllable. 23 At the same time, there are few data processing contents related to the numerical simulation of cumulative blasting, and it is impossible to express the characteristic law of multi-factor affecting the effect of cumulative blasting. This will require the application of reasonable methods to optimize the structural design of cumulative blasting, enhance the controllability of crack propagation after blasting, and apply a series of mathematical algorithms to couple the factors affecting the cracking effect of cumulative blasting.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%